Functional properties of hemoglobin and whole blood in an aquatic mammal, the Amazonian manatee (Trichechus inunguis) - Farmer, Martha C.; Weber, Roy Edwin; Bonaventura, Joseph; Best, Robin C.; Domning, Daryl Paul (Comparative Biochemistry and Physiology -- Part A: Physiology, 1979)
1. 1. Hematocrit (43%) and O2 binding capacity (18.8 ml O2/100 ml blood) of Trichechus inunguis blood are low compared to the values for other diving mammals but are similar to those for land mammals. 2. 2. Stripped manatee Hb is similar to human Hb A in its sensitivity to pH, 2,3-diphosphoglycerate and CO2, but less sensitive to temperature and more prone to dissociate into dimers. 3. 3. The unique Hill plots exhibit no cooperativity below 30% O2-saturation indicating a highly stabilized T or low-affinity state(s); such asymmetric Hill plots together with biphasic O2-binding kinetics could mean chain heterogeneity. 4. 4. The pH dependence of oxygen binding by the apparent T state, hemoglobin as seen in the Hill plots, is enhanced by 2,3-diphosphoglycerate but eliminated by CO2. © 1979.
Keywords: Hemoglobin; Animals Experiment; Blood; Blood And Hemopoietic System; Fish